Electrochemiluminescence Aptasensor for Profenofos Detection Based on Silver Nanoparticles Enhanced Luminol Luminescence System. Issue 15 (11th November 2019) - Liu, Huimin; Cheng, Shuting; Shi, Xiaojie; Zhang, Hui; Zhao, Qingxue; Dong, Haowei; Guo, Yemin; Sun, Xia
Abstract : In this work, an electrochemiluminescence (ECL) aptasensor based on silver nanoparticles (AgNPs) for detection of profenofos was presented. The aptasensor was based on the affinity of the aptamer (Apt) with the target profenofos. When the Apt contacted with the profenofos, the ECL detection signals were weakened, indicating the successful construction of the aptasensor. In order to improve the aptasensor performance, the platinum electrode (PE) was modified by AgNPs due to their good conductivity and catalytic property. Meanwhile luminol-hydrogen peroxide was selected as a luminescence system. Through the standard curve experiment and specificity experiment, it was proved that the sensor had the advantages of low detection limit and good specificity. Under the optimum conditions, the aptasensor had a good linear response to profenofos from 0.5 μg/mL to 100 μg/mL (1.34 μM to 267.6 μM ), with a low detection limit of 0.13 ng/mL and a correlation coefficient (R²) of 0.9903. The aptasensor was also successfully applied for detection of profenofos in real vegetables. Because the developed aptasensor had the following advantages of simple preparation, good stability, high selectivity and sensitivity, it would show great potential for other small molecule contamination detection.